(untitled) (International Journal of Medical and Surgical Sciences, 2014)
The objective of this research was to determine the type of management of symptomatic gallbladder lithiasic disease (GLD) in the Obrero Hospital No. 1, Bolivia. A Case Series study design from January to December 2013 was conducted. The prevalence of GLD in pregnant patients was 4.2% (18 patients), of which 12 (66.7%) were operated and 6 patients (33.3%) subjected to medical treatment. The mean age was 28.83 years (SD± 5.328). The preoperative diagnoses were acute or exacerbated GLD in 12 cases (66.6%), acute pancreatitis of lithiasic origin in 3 (16.7%) and obstructive jaundice due to choledocholithiasis in 3 cases (16.7%). The mean gestational age was 16.83 weeks (SD± 8.155). During the first trimester of pregnancy 5 cases (27.7%) were observed; during the second quarter 10 cases (55.6%) and 3 cases (16.7%) during the third trimester. Only 3 cases (16.6%) were nulliparous. Average leukocyte count was 10632 x mm³ (SD± 2748.038), and 66% had leukocytosis and left deviation. Of the 12 operated, 10 laparoscopic cholecystectomy were described and in two cases also bile duct exploration was performed. Balanced general anesthesia was used in 10 cases (83.4%), in one TIVA (total intravenous anaesthesia) (8.3%) and one spinal (8.3%). The pneumoperitoneum always performed with open Hasson technique. The average operative time was 47.5 minutes (SD± 16.989) and hospital stay of 5.44 days (SD± 3.568). Comparing stay, patients undergoing surgery have a longer hospital stay compared with those who received medical treatment (6.16 vs. 4 days). No fetal complications occurred, including maternal and fetal mortality or premature contractions requiring treatment. Laparoscopic surgery appears to be a safe option and may be the form of treatment when the GLD is persistently symptomatic, preferably during the second trimester of pregnancy.